Gathering at the top? Environmental controls of microplastic uptake and biomagnification in freshwater food webs. (1st January 2021) - Krause, Stefan; Baranov, Viktor; Nel, Holly A.; Drummond, Jennifer D.; Kukkola, Anna; Hoellein, Timothy; Sambrook Smith, Gregory H.; Lewandowski, Joerg; Bonet, Berta; Packman, Aaron I.; Sadler, Jon; Inshyna, Valentyna; et al.
Abstract: Microplastics are ubiquitous in the environment, with high concentrations being detected now also in river corridors and sediments globally. Whilst there has been increasing field evidence of microplastics accumulation in the guts and tissues of freshwater and marine aquatic species, the uptake mechanisms of microplastics into freshwater food webs, and the physical and geological controls on pathway-specific exposures to microplastics, are not well understood. This knowledge gap is hampering the assessment of exposure risks, and potential ecotoxicological and public health impacts from microplastics. This review provides a comprehensive synthesis of key research challenges in analysing the environmental fate and transport of microplastics in freshwater ecosystems, including the identification of hydrological, sedimentological and particle property controls on microplastic accumulation in aquatic ecosystems. This mechanistic analysis outlines the dominant pathways for exposure to microplastics in freshwater ecosystems and identifies potentially critical uptake mechanisms and entry pathways for microplastics and associated contaminants into aquatic food webs as well as their risk to accumulate and biomagnify. We identify seven key research challenges that, if overcome, will permit the advancement beyond current conceptual limitations and provide the mechanistic process understanding required to assess microplastic exposure, uptake, hazard, and overall risk to aquatic systems and humans, and provide key insights into the priority impact pathways in freshwater ecosystems to support environmental management decision making. Graphical abstract: Image 1 Highlights: Environmental risks are affected by pathway-specific exposures to microplastics. Particle properties and flow dynamics control exposure to microplastics. We identify uptake mechanisms and microplastic entry points into aquatic food webs. Ecotoxicological impacts are controlled by fate and transport of microplastics.